Trace elements and stable isotopes in penguin chicks and eggs: A baseline for monitoring the Ross Sea MPA and trophic transfer studies - Calizza E.; Signa G.; Rossi L.; Vizzini S.; Careddu G.; Tramati C. D.; Caputi S. S.; Mazzola A.; Costantini M. L. (Marine Pollution Bulletin, 2021)
Multi-tissue trace elements (TEs), C, N concentrations and stable isotopes (δ13C, δ15N) of chick carcasses and eggs of Adélie and Emperor penguins were studied to i) provide reference data before the recent institution of the Ross Sea Marine Protected Area (Antarctica), and ii) provide conversion factors that allow estimating C, N, δ13C and δ15N in edible tissues from non-edible ones, thus improving the use of stable isotopes in contamination and trophic transfer studies. Higher concentrations of As, Cd, Cr, Cu, Hg, Mn and Pb were found in chick carcasses than in eggs, suggesting increasing contamination in recent decades and high toxicity risks for penguin consumers. Isotopic conversion factors highlighted small differences among body tissues and conspecifics. These values suggest that chick carcasses are reliable indicators of the energy pathways underlying the two penguin species, their trophic position in the food web and their exposure to TEs.